2009
DOI: 10.1038/nature07952
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria hijack integrin-linked kinase to stabilize focal adhesions and block cell detachment

Abstract: The rapid turnover and exfoliation of mucosal epithelial cells provides an innate defence system against bacterial infection. Nevertheless, many pathogenic bacteria, including Shigella, are able to surmount exfoliation and colonize the epithelium efficiently. Here we show that the Shigella flexneri effector OspE (consisting of OspE1 and OspE2 proteins), which is highly conserved among enteropathogenic Escherichia coli, enterohaemorrhagic E. coli, Citrobacter rodentium and Salmonella strains, reinforces host ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
164
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 37 publications
6
164
0
Order By: Relevance
“…We speculate that VASP-mediated modification of focal adhesions inhibits Shigella recruitment of critical focal adhesion components to protrusions. As the efficiency of Shigella spread is directly correlated with the stabilization of focal adhesions and reduction in focal adhesion turnover (Kim et al, 2009), a mechanism that theoretically could contribute to the observed phenotype is a relative increase in focal adhesion turnover, associated with increased phosphorylation of focal adhesion kinase and paxillin, although whether VASP modulates focal adhesion turnover or stability is currently unclear. Mena, but not VASP, promotes clathrin-mediated uptake of Shigella protrusions in recipient cells (Fukumatsu et al, 2012); our data indicating that the role of the VASP EVH1 domain in restriction of spread is largely in the recipient cell raise the possibility that VASP competitively inhibits Mena function in this process.…”
Section: Vasp Derivatives Defective In Phosphorylation Atmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that VASP-mediated modification of focal adhesions inhibits Shigella recruitment of critical focal adhesion components to protrusions. As the efficiency of Shigella spread is directly correlated with the stabilization of focal adhesions and reduction in focal adhesion turnover (Kim et al, 2009), a mechanism that theoretically could contribute to the observed phenotype is a relative increase in focal adhesion turnover, associated with increased phosphorylation of focal adhesion kinase and paxillin, although whether VASP modulates focal adhesion turnover or stability is currently unclear. Mena, but not VASP, promotes clathrin-mediated uptake of Shigella protrusions in recipient cells (Fukumatsu et al, 2012); our data indicating that the role of the VASP EVH1 domain in restriction of spread is largely in the recipient cell raise the possibility that VASP competitively inhibits Mena function in this process.…”
Section: Vasp Derivatives Defective In Phosphorylation Atmentioning
confidence: 99%
“…Focal adhesions are dynamic complexes containing w50 proteins that actively participate in cell migration by connecting contractile cytoskeletal elements to the plasma membrane and transmitting the force that is generated to the extracellular matrix (Lo, 2006;Plotnikov & Waterman, 2013). The number and stability of focal adhesions contribute to cell-to-cell spread of Shigella, and components of focal adhesions are recruited to bacterial protrusions and sites of entry (Kim et al, 2009;Mounier et al, 1999).…”
Section: Vasp Derivatives Defective In Phosphorylation Atmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (Kim et al 2009). Reinforcement of cell adhesion to the matrix may represent an important factor during infection, by preventing their clearing in the intestinal lumen (Kim et al 2009). …”
Section: Preserving the Epithelium Integrity To Allow Disseminationmentioning
confidence: 99%
“…Another T3S effector, OspE, binds to ILK (integrin-like kinase) to stabilize integrin-dependent attachment of the cell to the basal matrix ( Fig. 1) (Kim et al 2009). Reinforcement of cell adhesion to the matrix may represent an important factor during infection, by preventing their clearing in the intestinal lumen (Kim et al 2009).…”
Section: Preserving the Epithelium Integrity To Allow Disseminationmentioning
confidence: 99%